Hubungan Komunikasi Perawat dengan Tingkat Kecemasan Keluarga Pasien di Unit Perawatan Kritis - Retnaningsih, Dwi (Jurnal Keperawatan Soedirman, 2016)
Anxiety will be more clearly observed among patients and families in the Critical Care Unit. Nurses can provide understanding and therapeutic approach to patients and their familia are realized with the implementation of effective communication between nurses with patients and their families throughtherapeutic communication. This study is to know the therapeutic nurse communication relationships with family anxiety levels of patients undergoing treatment at the Salatiga Hospital Critical Care Unit. A descriptive study design was conducted to investigate 24 samples. Spearman Rank test was administered to examine the correlation between nurse therapeutic communication and family’s anxiety. Results revealed that mostly nurse performed a good therapeutic , while patient’s family suffered from mid (66.7%) to severe 4.2% anxiety. There was no significant relationship between therapeutic communication and famili’s anxiety ((r= - 0,213; p:0.319). We suggested nurses to improve the quality of nursing services in particular on the attitudes and skills in communicating that nurses do.